DETERMINATION OF STEAM-BOILER PIPES FILTHINESS IN THERMAL POWER PLANTS - Stojanović, B. (Journal of Engineering & Processing Management, 2016)
A reliable operation of the equipment is primarily important for each installation. One of the measures of safe operation steam-boiler systems is purity pipes. Very acceptable method of determining the soiling pipe is a method of staining.In this paper is described the determination of soiling boiler tubes in power plant Ugljevik after a decade of operation of the plant.